The mind of the leader : how to lead yourself, your people, and your organization for extraordinary results - Hougaard, Rasmus; Carter, Jacqueline (Consultant) (Tantor Audio, 2018)
Using real-world inspirational examples from Marriott, Accenture, McKinsey & Company, LinkedIn, and many more, this must-listen guide redefines what it takes to be an effective leader.